2012
DOI: 10.5173/ceju.2012.04.art6
|View full text |Cite
|
Sign up to set email alerts
|

PEDIATRIC UROLOGY High efficacy of biofeedback therapy for treatment of dysfunctional voiding in children

Abstract: IntroductionDysfunctional voiding is a frequent condition in children associated with symptoms of incontinence. The aim of this study was to present the efficacy of biofeedback treatment on the resolution of clinical symptoms in a large cohort of children with urodynamically confirmed dysfunctional voiding.Material and methods81 children (75 girls and 6 boys) aged 6-18 years (mean: 10.32 ±3.17 yrs.) with a dysfunctional voiding pattern are presented. 74/81 (92.6%) of children were unresponsive to standard urot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
(33 reference statements)
0
11
0
1
Order By: Relevance
“…Similarly, another study by Kibar and colleagues reported a significant improvement in outcomes in children with DV using combined urotherapy plus biofeedback compared with standard urotherapy ( 2 ). Another study reported that symptomatic healing was observed in 50% of children with urotherapy - resistant DV who were treated with biofeedback ( 21 ). In recent years, biofeedback therapy has been increasingly used in children with DV.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study by Kibar and colleagues reported a significant improvement in outcomes in children with DV using combined urotherapy plus biofeedback compared with standard urotherapy ( 2 ). Another study reported that symptomatic healing was observed in 50% of children with urotherapy - resistant DV who were treated with biofeedback ( 21 ). In recent years, biofeedback therapy has been increasingly used in children with DV.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively high percentage of children on anticholinergics may also account for the less pronounced effect compared to prior studies. [16,22,26,27] The limitations of the present study are the relatively small patient cohort, a short followup period, the non-controlled study design and the lack of any symptom questionnaire J o u r n a l P r e -p r o o f data or voiding diaries. Also, 7% of the children were assessed not to be adequately treated for constipation at the commence to treatment, and some children were on other medications including prophylactic antibiotics and anticholinergics during treatment, which could influence the results.…”
Section: Discussionmentioning
confidence: 91%
“…The other 8 studies 18,19,23,24,[27][28][29][30] can only be qualitatively analyzed because of the incomplete results.…”
Section: Literature Searchmentioning
confidence: 99%
“…In addition, seven studies 19,23,24,[27][28][29][30] didn't provide initial values before standard treatment and one study 18 didn't report results at the endpoint of 6 or 12 months, so we could only perform qualitative analysis on them. The results are shown in Table 4.…”
Section: Increase Of Max Urinary Flow Ratementioning
confidence: 99%